2022
DOI: 10.1155/2022/2822605
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity Evaluation of Metformin in Freshwater Planarian Dugesia japonica by the Comet Assay and RAPD Analysis

Abstract: Objective. To investigate the genotoxicity of metformin on planarian with different concentrations and exposure times. Methods. The planarians were treated, respectively, with 10 mmol/L and 50 mmol/L metformin for 1, 3, and 5 days, and then, the comet assay and random amplified polymorphic DNA (RAPD) analysis were performed. 13 random primers were used for PCR amplification with the genomic DNAs as templates. Planarians cultured in clear water were used as the control. Genomic template stability (GTS) was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Some studies have suggested that metformin's antioxidant effects may help protect against DNA damage caused by oxidative stress in fish. Our findings are supported by the fact that planarians exposed to 10 mmol/L of metformin for 1, 3, and 5 days exhibited 10.2%, 25.4%, and 36.8% increases in DNA damage, whereas planarians exposed to 50 mmol/L of metformin experienced increases of 40.6%, 62.8%, and 65.4% in DNA damage [31]. The research on the effects of metformin on DNA damage in fish is still limited, and more studies are needed to fully understand the potential risks.…”
Section: Genotoxicitysupporting
confidence: 81%
See 1 more Smart Citation
“…Some studies have suggested that metformin's antioxidant effects may help protect against DNA damage caused by oxidative stress in fish. Our findings are supported by the fact that planarians exposed to 10 mmol/L of metformin for 1, 3, and 5 days exhibited 10.2%, 25.4%, and 36.8% increases in DNA damage, whereas planarians exposed to 50 mmol/L of metformin experienced increases of 40.6%, 62.8%, and 65.4% in DNA damage [31]. The research on the effects of metformin on DNA damage in fish is still limited, and more studies are needed to fully understand the potential risks.…”
Section: Genotoxicitysupporting
confidence: 81%
“…Today, there are more genotoxic pollutants than ever in the aquatic environment, spurring researchers to create rapid monitoring tools. Due to their accessibility, speed, and sensitivity, comet test methodologies are frequently used in ecotoxicology and biomonitoring [31]. Direct DNA damage may occur when environmental contaminants, such as pharmaceutical medications, combine with aquatic creatures; indirect DNA damage can occur when these toxins generate reactive oxygen species (ROS), which have the potential to disrupt the consistency of DNA pieces.…”
Section: Genotoxicitymentioning
confidence: 99%
“…Randomly amplified polymorphic DNA (RAPD) is a technique for polymorphism analysis of genomic DNA, which is often used for the detection of genetic diversity and genotoxicity analysis ( Pandey, Nagpure & Trivedi, 2018 ; Zare et al, 2019 ; Zhou et al, 2011 ). It is an important method for detecting the genotoxicity of drugs and pollutants to planarians ( Yin et al, 2022 ; Zhang et al, 2016b ). However, the application of RAPD technology for detecting the genotoxicity of SDS to planarians has not been reported.…”
Section: Introductionmentioning
confidence: 99%